PELAKSANAAN TUGAS DAN FUNGSI BIDANG PENCEGAHAN BNNP RIAU DALAM UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOTIKA - Hanna, Putri Merysa; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The National Narcotics Department (BNN) is a Non Government Agencies Ministry (LPNK) Indonesia, which duties are prevention, eradication of abuse and illicit traffic in psychotropic, precursors, and other addictive substances except for the addictive ingredients of tobacco and alcohol. Provincial National Narcotics Division (BNNP Riau) carries out the duties, functions, and BNN authorities within the province. Based on the phenomenon and the fact, this research is conducted on the implementation of duties and functions of BNNP Prevention Divition In Narcotics Abuse Prevention .The purpose of this research is to determine the implementation of duties and functions of BNNP Prevention Division In Narcotics Abuse Prevention, and to identify the factors that affect the implementation of duties and functions of BNNP Prevention Division In Narcotics Abuse Prevention. The theory that is used as a analysis tool in this research is the theory of Ig. Wursanto (2005) on the organization elements, while the method is qualitative descriptive research that is intended to provide a systematic overview of the observed phenomenon.Based on the results of research in the field of implementation of duties and functions of BNNP Prevention Division In Narcotics Abuse Prevention, BNNP Riau has completed it organizationally, where in completing the duties, BNNP Riau is quite able to do the functions properly. It can be seen from the Man (human) indicators, eventhough BNNP Riau has less personnel but on the environmental indicators, the implementation of duties keep running. The obstacle factors in carrying out the duties and functions of BNNP Riau prevention in preventing narcotics abuse is the lack of personnel, the lack of cooperation with external parties, and the lack of existing equipment in BNNP Riau, these conditions will result the performance of BNNP Riau implementation of duties and functions are not maximally carried out.Keywords : Implementation of Duties and Functions, Narcotics